The impact of technology application in the improvement of service delivery: a case study at the Road Transport Department Malaysia law enforcement division of Pulau Pinang - Hilmi Rasyad, Mohd Hassan (2013)
This study is an attempt to learn the impact of ICT in service delivery with the special focus on Road Transport Department (JPJ) Malaysia. It deals with the service sector that implements ICT infrastructure to enhance the services being produced by the application of technology. This study aims to understand effectiveness of e-services in terms of improvement in service delivery. The effectiveness of services delivered is recognized through the time factor by delivering time effective services. This study also tries to understand the level of technology absorption of the organization, and do technology application influence the effectiveness of service provided. The technology application means the ICT infrastructure implementation by the department. In other words, the improvement in service delivery is analysed through effectiveness of services to identify the influences of the factors on service delivery improvement. A qualitative method was being used as the research data collection method that has a combination of content analysis, using historical data and survey through in-depth interview. The findings of this study show that the effectiveness of e-services is influenced by time factor. The findings also show that the contributing factor of ICT infrastructure, infrastructure maintenance influences the effectiveness of the services. Meanwhile, the customer satisfaction ensures the effectiveness of services provided. Therefore, the results show that the contributing factors have significant relationship with service delivery improvement.